PENGARUH PENGETAHUAN PERPAJAKAN, KESADARAN WAJIB PAJAK DAN SANKSI PERPAJAKAN TERHADAP KEPATUHAN WAJIB PBB-P2 PADA BAPENDA JAKARTA TIMUR TAHUN 2020 - Patriandari -; Hana Amalia (Fakultas Ekonomi dan Bisnis Universitas Islam As-Syafi'iyah, 2022)
This study aims to determine the effect of tax knowledge, taxpayer awareness and tax sanctions on PBB-P2 Compulsory Compliance at the East Jakarta Bapenda 2020. The population in this study is all land and building taxpayers in East Jakarta City. The number of research samples used was 100 respondents who were selected by distributing questionnaires. This data was obtained by analysis technique using SEM-PLS (Structural Equation Modeling - Partial Least Squares) through SmartPLS 3.0 software. The period in this study is 2021. The results show that tax knowledge and awareness of taxpayers have a significant positive effect on PBB-P2 Compulsory Compliance, while tax sanctions have no significant effect on PBB-P2 Compulsory Compliance in East Jakarta City. Suggestions in this study is that it is necessary to improve the quality of tax sanctions so that it will increase taxpayer compliance in fulfilling tax obligations in East Jakarta City.